Keterlibatan Negara-negara Besar dalam Perdagangan Senjata: Studi Kasus Peran Amerika Serikat dan Rusia dalam Memperkuat Militer Arab Saudi - Rachman, Shiva Faizah Aulia; Nadirah, Kamilia; Nisa', Afifatun; Firda Fatikha Krisna (Future Science, 2024)
The results of this study show that Saudi Arabia's military has been greatly strengthened by the participation of the United States and Russia in the arms trade. Saudi Arabia's defense capabilities have been strengthened by the United States and Russia through the supply of cutting-edge weapons and military cooperation agreements. According to the data collected, the two countries control most of Saudi Arabia's arms industry. The United States is the main provider of fighter jets and air defense systems, while Russia contributes missile systems and other military technology. These findings demonstrate the strategic importance that the arms trade of major countries has in strengthening Saudi Arabia's military dominance in the Middle East. Moreover, the impact of this arms trade on regional geopolitical dynamics is also revealed in this study. The United States and Russia have a major role in strengthening Saudi Arabia's military, which not only affects Middle Eastern power dynamics but also strengthens their bilateral relations with Saudi Arabia. The results of this study prove that major powers can effectively maintain and increase their influence in a vital region through diplomacy via the arms trade, apart from economic issues.